PENERAPAN MODEL PEMBELAJARAN PROBLEM POSING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA POKOK BAHASAN IKATAN KIMIA DI KELAS X MIPA SMAN 4 PEKANBARU - Nurfadhillah Nurfadhillah; Asmadi M Noer; Erviyenni Erviyenni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purposes of research are to know the improvement of student learning outcomes by implementing problem posing learning model on the subject of chemical bonds in class X MIPA SMAN 4 Pekanbaru.. This research is experimental research using Design Randomized Control Group Pretest-Posttest. The population in the research consist of 4 class, that is X MIPA 1, X MIPA 2, X MIPA 3 and X MIPA 4. The research sample consisted two class, class X MIPA 4 as experiment class and class X MIPA 2 as control class that has tested by normality test using Liliefors test and homogeneity test using equality of two average test. Hypothesis was done by using test-t right side to choiced the improvement category of student achievement. Research result shown that the implementation of problem posing learning model can improve student learning outcomes on the chemical bonds subject where tarithmetic = 2,07 > ttable = 1,67.Key Words: Learning Model Problem Posing, Learning Outcomes, Chemical Bonds